The Influence of Brand Image and Attributes of Passenger Cars on Purchase Decisions through Online Consumer Review - Ivan Prihatno; Bambang Supriadi; Sina Setyadi; Hadiansyah Hadiansyah (Innovation Business Management and Accounting Journal, 2024)
The increasing economic growth after COVID-19 has encouraged high consumption of automotive products, coupled with the development of information on social media, making Mitsubishi Xpander products increasingly popular in the Greater Malang area. This research aims to determine the influence of brand image and passenger car attributes on purchasing decisions through online consumer reviews of consumers purchasing Mitsubishi Xpander cars and taking samples from 145 respondents, using non-probability for all PT consumers. Using the SEM-PLS analysis method, Sun Star Motor Singosari Malang purchases in October, November, and December 2023 and January, February and March 2024. The research results show that brand image does not affect purchasing decisions, passenger car attributes affect purchasing decisions, brand image has a significant effect on online consumer reviews, passenger car attributes have an effect on online consumer reviews, online reviews have an effect on purchasing decisions, brand image has an effect on purchasing decisions through online consumer reviews, and passenger car attributes influence purchasing decisions through online consumer reviews when purchasing a Mitsubishi Xpander car at PT. Sun Star Motor Singosari Malang.